Respuesta :

Answer:
y=(x-6)^2-21

Explanation:
To complete the square, the same value needs to be added to both sides

y+?=x^2-12x+?+15

To complete the square x^2-12x+36=(x-6)^2 add 36 to the expression

y+?=x^2-12x+36+15

Since 36 was added to the right-hand side, also add 36to the left-hand side

y+36=x^2-12x+36+15

Use a^2-2ab+b^2=(a-b)^2 to factor the expression

y+36=(x-6)^2+15

Move the constant to the right-hand side and change its sign

y=(x-6)^2+15-36

Calculate the difference

y=(x-6)^2-21